DESIGN AND IMPLEMENTATION OF A DATA COLLECTION SYSTEM WITH RASPBERRY PI FOR GREENHOUSE MONITORING - Plytas, Antonios-Fanourios (My University, 2014)
The need to produce high quality vegetables or flowers throughout the whole year, led to the development of automated greenhouses. Automation systems contribute to achieve the optimal conditions indoor, enable to be monitored and controlled from distance. Measurements such as humidity and temperature are critical for plantation growth thus they need to be accurately monitored and controlled. The aim of the thesis is the design and implementation of a data collection system in a greenhouse using two most popular programmable boards, Raspberry Pi and Arduino Uno. The system collects data of the most essential parameters, as humidity and temperature, which contribute to the desired climate. To control temperature and humidity, a fully automated ventilation system maintains the greenhouse’s interior to optimal conditions. The humidity and temperature measurements are stored in a SQLite database, which is installed on the Raspberry PI. Over a dynamic webpage the data can be retrieved from almost every place in the world.
Keywords: Greenhouse; Raspberry Pi; Arduino Uno; SQLite.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|